Community acceptance of environmental larviciding against malaria with Bacillus thuringiensis israelensis in rural Burkina Faso - A knowledge, attitudes and practices study - Peter Dambach; Issouf Traoré; Hélène Sawadogo; Pascal Zabré; Sharvari Shukla; Rainer Sauerborn; Norbert Becker; Revati Phalkey (Taylor & Francis Group, 2021)
Background Malaria control is based on early treatment of cases and on vector control. The current measures for malaria vector control in Africa are mainly based on long-lasting insecticidal nets (LLINs) and to a much smaller extent on indoor residual spraying (IRS). While bed net use is widely distributed and its role is intensively researched, Bti-based larviciding is a relatively novel tool in Africa. In this study, we analyze the perception and acceptability of Bti-based larval source management under different larviciding scenarios that were performed in a health district in Burkina Faso. Objective To research people's perception and acceptance regarding biological larviciding interventions against malaria in their communities. Methods A cross-sectional study was undertaken using a total of 634 administered questionnaires. Data were collected in a total of 36 rural villages and in seven town quarters of the semi-urban town of Nouna. Results Respondents had basic to good knowledge regarding malaria transmission and how to protect oneself against it. More than 90% reported sleeping under a bed net, while other measures such as mosquito coils and insecticides were only used by a minority. The majority of community members reported high perceived reductions in mosquito abundance and the number of malaria episodes. There was a high willingness to contribute financially to larviciding interventions among interviewees. Conclusions This study showed that biological larviciding interventions are welcomed by the population that they are regarded as an effective and safe means to reduce mosquito abundance and malaria transmission. A routine implementation would, despite low intervention costs, require community ownership and contribution.